A Chatbot that uses Artificial Intelligence to Automatically Respond to Whatsapp Messages (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
The recent advancement trend of the technology had motivated the need for the study to explore the readiness of the employees in the workplace in accepting the new technology engagement. With this, the current study will focus on investigating the readiness of the employees towards the social interaction with the technology in the workplace in Malaysia. The previous study had suggested that there is indication of the social interaction among employees to have positive relationship against the acceptance of the technology at workplace which provide the indication that the employees are not ready for the shift into the digitalization era of working environment. The quantitative analysis method had been taken into the account for the methodology of the research where the quantitative analysis will focus on the output based on the 150 questionnaires distribution among the Malaysian employees based on the convenience sampling. The outcome of the result through the quantitative analysis had observe the lack of evidence to prove the presence of the significant in the relationship between the social interaction of the employee towards the acceptance of the technology in the workplace. This had been providing the evidence to show that the Malaysian employees had been not affected by the social interaction factor when comes to the transitioning towards the engagement of new technology in the workplace provide the indication that the Malaysian employees are likely to be ready for the shift into the transitioning and shift into the use of technology in the workplace.